Reproductive technologies in farm animals [ - Gordon, Ian , 1928- (CABI Publications and Resources, 2004)
In the past half century great progress has been made in the reproductive management of farm animals, both mammals and birds. This book aims to review developments and indicate which reproductive technologies can be used commercially or in research. It egins by discussing artificial insemination and how this has recently been refined in semen sexing technology. Embryo transfer, in vitro embryo production technology and the control of oestrus and ovulation are then reviewed. Subsequent chapters consider the control of postpartum ovarian activity, seasonal breeding, multiple births and litter size, pregnancy testing, parturition, and the onset of puberty. The author then describes more recent developments in cloning and the production of transgenic animals, before a final chapter on suppressing reproductive activity.